Lung ultrasound for the diagnosis of pneumonia in adults - admin; Isik Melike Unlukapla; Halil Dogan; Dogac Niyazi Ozucelik (Journal of the Pakistan Medical Association, 2020)
Objective: To investigate the value of chest ultrasound in the diagnosis of pneumonia in adults. Methods: The prospective observational cohort study was conducted at Bakirkoy Dr. Sadi Konuk Training and Research Hospital, Istanbul, Turkey, from December 1, 2015,to March 1, 2016, and comprised suspected pneumonia patients aged >18 years. Sonographic pneumonia was defined as lung consolidation with air bronchograms. Treating clinicians were blinded to lung ultrasound results. All patients who were advised to undergo thoracic computerised tomography after physical examination were subjected to posteroanterior chest X-ray before the scan. Patients in whom pneumonia was detected in the scan underwent thorax ulstasonography according to Bedside Lung Ultrasound in Emergency protocol. Follow-up was done with medical record review to obtain the final diagnosis and antibiotic usage. Data was analysed using SPSS 22. Results: Of the 125 patients, 61(48.8%) were male. The overall mean age was 73.9±14.6 years. In 97(77.6%) patients, pneumominal infiltration was detected by thorax ultrasound, and in 57(45.6%) the infiltration was detected with chest X-ray. Conclusion: Thorax ultrasound was found to be a helpful diagnostic method when performed according to the Bedside Lung Ultrasound in Emergency protocol.